PENGARUH PENGAWASAN, EVALUASI DAN AUDIT KINERJA KARYAWAN TERHADAP LOYALITAS ANGGOTA BMT BERKAH TRENGGALEK (An-Nisbah: Jurnal Ekonomi Syariah, 2016)
This research aims is to know the infuence of employee monitoring, employee evaluation and performance audit against the loyalty of members. This research is at BMT Blessing Trenggalek. Samples taken in this study was 50 respondents. Sampling with probability techniques using random sampling. Measurements in this study using a Likert scale. Methods of data analysis used is multiple regression with the help of the program SPSS version 20.The results showed that monitoring employees against the loyalty of infuential members in a positive and not signifcant according to statistics on the BMT Berkah Trenggalek. Research results show that employee evaluation against the loyalty of infuential members are negative and not signifcant according to statistics on the BMT Berkah Trenggalek. Research results show that the performance audit of employees against the loyalty of infuential members in a positive and not signifcant according to statistics on BMT Berkah Trenggalek. In the same crucible of employee monitoring, employee evaluation and performance audit of the employees does not affect the loyalty of members. That means that together equal a third of these factors do not affect the loyalty of members on BMT Berkah Trenggalek. Keyword: Employee Monitoring, Employee Evaluations, performance.Audit and loyalty Members